Mapping of Leading Commodities in the Agricultural Sector in Buol Regency Using a Geographic Information System - Rival Rahman; Mohammad Zubair Hippy; Wila Rumina Nento (Cita konsultindo, 2024)
The agricultural sector is an important sector in a region because it is the main milestone of the community's economy, including in Buol Regency. This study aims to analyze and map the distribution of the agricultural base sector in Buol Regency with the help of Geographic Information System (GIS) analysis. The research method used is a quantitative descriptive approach with Location Quotient (LQ) analysis techniques, localization analysis, and specialization analysis. The analysis is supported by primary data and secondary data obtained from various sources, both government and private agencies. The results of the LQ analysis show that rice fields and corn are the main commodities that have the widest distribution of advantages, while other commodities tend to be superior in certain regions. Localization analysis shows that all agricultural commodities have a relatively even distribution pattern and are not concentrated in one area. Meanwhile, the analysis of specialization shows that only paddy rice is classified as a special commodity, while other commodities have not shown a high level of regional specialization. Thus, it can be concluded that paddy rice is a commodity based on the agricultural sector in Buol Regency which is spread almost throughout the sub-district.